A Simple Synthesis of Fe2P Nanoparticles Encapsulated Doped Carbon Nanotube as Electrocatalysts for Oxygen Reduction Reaction and Zinc‐Air Battery. Issue 2 (4th December 2021) - Sun, Tiantian; Li, Suriguga; Li, Tianjiao; Chen, Xinyu; Xu, Dan; Wang, Heng-guo
Abstract : The design and application of high efficiency, low cost, and nonprecious metal oxygen reduction reaction (ORR) catalyst is a prerequisite for the commercialization of energy conversion devices. Here, a simple method is proposed to prepare Fe2 P nanoparticles encapsulated in nitrogen‐doped carbon nanotubes (Fe2 P@NPCNTs) through a self‐growth strategy. In addition, it is worth noting that Fe2 P@NPCNTs have high catalytic activity and good stability as ORR catalysts due to the unique structure of the material, the synergy between the components, and the large specific surface area. As expected, the catalyst has a half‐wave potential (0.827 V) close to commercial Pt/C and a lower Tafel slope (54.17 mV dec −1 ) compared to other samples. Meanwhile, the zinc‐air battery with Fe2 P@NPCNTs as catalysts exhibits high open‐circuit voltage, good maximum power density, and excellent stability. Therefore, this cheap and simple method is generally available for the synthesis of other non‐noble metal catalysts for various energy systems. Abstract : A simple metal–organic framework‐derived strategy is used to synthesize Fe2 P nanoparticles encapsulated in nitrogen‐doped carbon nanotubes, which can serve as high‐efficient electrocatalysts for the oxygen reduction reaction and zinc‐air batteries.